Activation of a passive, mesoporous silica nanoparticle layer through attachment of bacterially-derived carbon-quantum-dots for protection and functional enhancement of probiotics. (June 2022) - Wei, Hao; Geng, Wei; Yang, Xiao-Yu; Kuipers, Jeroen; van der Mei, Henny C.; Busscher, Henk J.
Abstract: Probiotic bacteria employed for food supplementation or probiotic-assisted antibiotic treatment suffer from passage through the acidic gastro-intestinal tract and unintended killing by antibiotics. Carbon-quantum-dots (CQDs) derived from bacteria can inherit different chemical groups and associated functionalities from their source bacteria. In order to yield simultaneous, passive protection and enhanced, active functionality, we attached CQDs pyrolytically carbonized at 220 ​°C from Lactobacillus acidophilus or Escherichia coli to a probiotic strain ( Bifidobacterium infantis ) using boron hydroxyl-modified, mesoporous silica nanoparticles as an intermediate encapsulating layer. Fourier-transform-infrared-spectroscopy, X-ray-photoelectron-spectroscopy and scanning-electron-microscopy were employed to demonstrate successful encapsulation of B. infantis by silica nanoparticles and subsequent attachment of bacterially-derived CQDs. Thus encapsulated B. infantis possessed a negative surface charge and survived exposure to simulated gastric fluid and antibiotics better than unencapsulated B. infantis . During B. infantis assisted antibiotic treatment of intestinal epithelial layers colonized by E. coli, encapsulated B. infantis adhered and survived in higher numbers on epithelial layers than B. infantis without encapsulation or encapsulated with only silica nanoparticles. Moreover, higher E. coli killing due to increased reactive-oxygen-species generation was observed. In conclusion, the active, protective encapsulation described enhanced the probiotic functionality of B. infantis, which might be considered as a first step towards a fully engineered, probiotic nanoparticle. Graphical abstract: Image 1 Highlights: B. infantis was encapsulated in silica nanoparticles, activated with bacterially-derived CQDs. Encapsulated B. infantis showed enhanced survival after exposure hostile conditions. CQD activation of encapsulated B. infantis enhanced ROS generation and pathogen killing. CQD activation of encapsulated B. infantis enhanced adhesion to intestinal epithelial layers.